BATTLEDRESS: USING IMMERSIVE DOCUMENTARY METHODS TO AERATE WORKING CLASS WOMEN’S ORAL HISTORY - Ballin, Deborah; Genn, Rachel (Brazilian Creative Industries Journal, 2023)
This case study reflects on a multi-disciplinary research project BATTLEDRESS that investigates how methodologies of oral history and archive can be entwined with immersive techniques to create alternative ‘encountered’ histories of marginalised working-class women’s experiences. The text reflects on a two-screen immersive film that draws on two oral testimonies with working class women writers reflecting on their teenage motivations for fighting and fashion choices and the little-explored themes of: Place and Belonging, Plenitude, Scarcity, Vulnerability, Invincibility, Femininity, Performance and Stepping Out that emerged from these. It discusses how working-class stories can be aerated through a layered two screen immersive approach where archive, audio/still and moving image sit in conversation with each other. These multiple iterations elicited unexpected findings and contradictions, encouraging the viewer/listener to delve into the underlying themes in the testimony, —prompting original insights into the confusion around gender roles and class uncertainty that can be at the heart of teenage female violence. It posits that experimenting with framing and eschewing a straightforward narrative can disrupt commonplace representations of grit, madness and despair whilst acknowledging the vulnerability, fragility, — but also ambitions and dreams of— the working-class teenage girl.